2018
DOI: 10.1167/iovs.18-24059
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Osteoporosis and Age-Related Macular Degeneration: The Korea National Health and Nutrition Examination Survey

Abstract: PURPOSE. Previous studies have reported a possible link between low bone mineral density and AMD. The aim of the present study was to investigate the association between osteoporosis and AMD in a South Korean cohort. METHODS. This cross-sectional, nationwide study included 3496 women and 2789 men who had participated in the Korean National Health and Nutrition Examination Survey from 2008 to 2011. All retinal photographs were graded using an international classification and grading system. Osteoporosis was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Currently, the estimate of osteoporosis is mainly by bone mineral density (BMD) measurement . However, this method has limitations since changes in bone density usually occur slightly . Thus, the exploration of more specific and sensitive biomarkers to identify osteoporosis is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the estimate of osteoporosis is mainly by bone mineral density (BMD) measurement . However, this method has limitations since changes in bone density usually occur slightly . Thus, the exploration of more specific and sensitive biomarkers to identify osteoporosis is needed.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, this method has limitations since changes in bone density usually occur slightly. 6,7 Thus, the exploration of more specific and sensitive biomarkers to identify osteoporosis is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, different clinical studies have drawn the conclusion that low BMD is linked to the progression of AMD. A Korean cohort study showed that osteoporosis was associated with AMD in women while no association with other age-related eye diseases [ 8 ]. A multicenter study in the United States demonstrated that higher levels of BMD may be associated with a lower risk for AMD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, osteoporosis is also linked to eye diseases, such as age-related macular degeneration (AMD). There are numerous studies in the literature which have shown that low bone mineral density (BMD) was significantly associated with the progression of AMD [ 8 ], while higher levels of BMD may be associated with a lower risk for AMD [ 9 ]. However, the mechanism is still intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…Females have longer life expectancies compared to those of males, regardless of their educational, economic, political, and health statuses [1,2]. Decreased estrogen production predisposes postmenopausal women to degenerative conditions, including cataracts and age-related macular degeneration [3][4][5][6][7][8]. In contrast, males are predisposed to open-angle glaucoma [9], diabetic retinopathy [10], and pigment dispersion glaucoma [11].…”
Section: Introductionmentioning
confidence: 99%